INHERENT SAFETY INDEX FOR PROTON MEMBRANE FUEL CELL VEHICLE SYSTEM (Jurnal Teknologi (Sciences & Engineering), 2016)
There are enormous numbers of indices being developed in process industries to describe, rank or quantify hazards to the people, properties and environments. Most indices are being applied to large scale and complex systems of process industries. Development of a swift and simple inherent safety index method which is relevant to small scale, less complex membrane fuel cell system particularly the one which to be applied during an early design stage is essential as an alternative to current comprehensive and yet time-consuming indices. In this work, a modified version of PIIS, modified prototype index for inherent safety (m-PIIS) was developed with the objectives of identifying, indicating and estimating inherent safety of fuel cell system at early design stage. The developed index was applied on four proton exchange membrane (PEM) fuel cell systems; high pressure PEMFC system, low pressure PEMFC system, LH2 PEMFC system and on-board Me-OH PEMFC system. The developed index was also benchmarked against the original PIIS and ISI using the published results for the selection of process routes in MMA production. Results have indicated that m-PIIS has strong positive relationship with PIIS and ISI on most of the reaction step in MMA with the most significant are the C4, TBA, and C3 reaction steps. Other reaction steps such as C2/MP, C2/PA and ACH showed a strong positive relationship as well